1986
DOI: 10.1073/pnas.83.17.6233
|View full text |Cite
|
Sign up to set email alerts
|

Protein sequencing by tandem mass spectrometry.

Abstract: Methodology for determining amino acid sequences of proteins by tandem mass spectrometry is described. The approach involves enzymatic and/or chemical degradation of the protein to a collection of peptides which are then fractionated by high-performance liquid chromatography. Each fraction, containing as many as 10-15 peptides, is then analyzed directly, without further purification, by a combination of liquid secondary-ion/collision-activated dissociation mass spectrometry on a multianalyzer instrument. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
762
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,163 publications
(768 citation statements)
references
References 17 publications
6
762
0
Order By: Relevance
“…Proline is in general known to induce very strong cleavage at its N-terminal site [20], whereas the cleavage at the C-terminal site is suppressed [21]. Smith et al [17] found that in the cationic peptide VPDPR cleavage C-terminal to the proline in the second position was unusually abundant and attributed this fact to cyclization of the first two residues into a diketopiperazine structure.…”
Section: Proline Effect In B 2 Ion Formationmentioning
confidence: 99%
“…Proline is in general known to induce very strong cleavage at its N-terminal site [20], whereas the cleavage at the C-terminal site is suppressed [21]. Smith et al [17] found that in the cationic peptide VPDPR cleavage C-terminal to the proline in the second position was unusually abundant and attributed this fact to cyclization of the first two residues into a diketopiperazine structure.…”
Section: Proline Effect In B 2 Ion Formationmentioning
confidence: 99%
“…Most tandem mass spectrometers currently applied to peptide cations employ multiple relatively low energy collisions as the means for parent ion excitation [11]. Under these conditions, CID induces amide backbone cleavage, producing b-and y-type ions [12,13], which are useful in polypeptide characterization [14]. A complication of using low energy CID to study polypeptide ions generated from ESI arises when disulfide bonds are present.…”
mentioning
confidence: 99%
“…Mass spectrometry has been widely used in the structure elucidation of biomolecules including peptides [13][14][15]. The effect of an acidic amino acid, i.e., aspartic acid, glutamic acid, and Cys-SO 3 H, on the fragmentation of protonated peptide ions has been well studied [16 -22].…”
mentioning
confidence: 99%